Engineered T cells for cancer therapy - June, Carl H.; Maus, Marcela V.; Plesa, Gabriela; Johnson, Laura A.; Zhao, Yangbing; Levine, Bruce L.; Grupp, Stephan A.; Porter, David L. (Cancer Immunology, Immunotherapy, 2014)
It is now well established that the immune system can control and eliminate cancer cells. Adoptive T cell transfer has the potential to overcome the significant limitations associated with vaccine-based strategies in patients who are often immune compromised. Application of the emerging discipline of synthetic biology to cancer, which combines elements of genetic engineering and molecular biology to create new biological structures with enhanced functionalities, is the subject of this focused research review.